The Sensorineural Hearing Loss Related to a Rare Infratentorial Developmental Venous Angioma: A Case Report and Review of Literature - Ebrahimzadeh, Kaveh; Tavassol, Hesameddin Hoseini; Mousavinejad, Seyed Ali; Ansari, Mohammad; Kazemi, Reyhaneh; Bahrami-Motlagh, Hooman; Jalili Khoshnoud, Reza; Sharifi, Guive; Samadian, Mohammad; Rezaei, Omidvar (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Developmental venous anomaly (DVA) is a benign venous abnormality draining normal brain parenchyma. It is mostly asymptomatic; however, rare complications such as hemorrhage may lead to symptomatic conditions. Headache and seizure are the most common symptoms. Hearing loss is an extremely rare presentation of DVA. To our knowledge, only five cases of DVA, presenting with hearing loss, had been reported so far.Case Presentation We report the case of a 27-year-old woman who presented with a sensorineural hearing loss followed by facial paresis. Magnetic resonance imaging (MRI) and computed tomography (CT) angiography revealed hematoma with adjacent converging veins showing a typical “caput medusa” sign in the left middle cerebellar peduncle, in favor of DVA. Due to the compression effect of hematoma, she underwent surgery. Hearing loss and facial paresis improved significantly during the postoperative follow-up.Conclusion Although DVA is mostly benign and asymptomatic, complications such as hemorrhage rarely occur. Hearing loss is an extremely rare presentation that can be attributable to the compression effect on the cranial nerve VII to VIII complex. In the case of compression effect or progression of symptoms, surgical intervention is necessary. A good clinical outcome could be expected postoperatively.
Keywords: venous angioma; middle cerebellar peduncle; pons; hearing loss; infratentorial; hemorrhage